1979
DOI: 10.1126/science.204.4391.407
|View full text |Cite
|
Sign up to set email alerts
|

γ-Aminobutyric Acid, a Neurotransmitter, Induces Planktonic Abalone Larvae to Settle and Begin Metamorphosis

Abstract: gamma-Aminobutyric acid (a simple amino acid and potent neurotransmitter in human brain and other tissues of higher animals) and certain of its congeners rapidly and synchronously induce planktonic larvae of the red abalone, Haliotis rufescens, to settle and commence behavioral and developmental metamorphosis. These naturally occurring inducers of algal origin apparently are responsible, in part, for the substrate-specific recruitment, induction of settling, and the onset of metamorphosis of abalone and other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
196
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 353 publications
(207 citation statements)
references
References 10 publications
7
196
0
Order By: Relevance
“…), and the differences between my estimates and the others may reflect the bias caused by estimating growth of newly settled invertebrates based on study of larger individuals. The general growth pattern described here -of a threshold size at which a juvenile switches to a different (adult) mode of feeding -applies to a variety of invertebrate taxa (abalone: Morse et al 1979, Shepherd & Turner 1985Aplysia: Sarver 1979;starfish: Birkeland et al 1971,Yamaguchi 1973, Barker 1979, Zann et al 1987). Young of several of these taxa associate with crustose coralline algae (Barnes & Gonor 1973, Yaniaguchi 1973, Barker 1979, Morse et al 1979, Shepherd & Turner 1985, Zann et al 1987, presumably because such algae slough the epithallial cell layer thereby providing food for these surface-feeding micro-grazers (Steneck 1986).…”
Section: Growthmentioning
confidence: 88%
“…), and the differences between my estimates and the others may reflect the bias caused by estimating growth of newly settled invertebrates based on study of larger individuals. The general growth pattern described here -of a threshold size at which a juvenile switches to a different (adult) mode of feeding -applies to a variety of invertebrate taxa (abalone: Morse et al 1979, Shepherd & Turner 1985Aplysia: Sarver 1979;starfish: Birkeland et al 1971,Yamaguchi 1973, Barker 1979, Zann et al 1987). Young of several of these taxa associate with crustose coralline algae (Barnes & Gonor 1973, Yaniaguchi 1973, Barker 1979, Morse et al 1979, Shepherd & Turner 1985, Zann et al 1987, presumably because such algae slough the epithallial cell layer thereby providing food for these surface-feeding micro-grazers (Steneck 1986).…”
Section: Growthmentioning
confidence: 88%
“…Larvae (0.2 mm) of the Pacific red abalone, Haliotis rufescens, a gastropod mollusc, are induced to settle, attach to substrata, and metamorphose by chemosensory recognition of y-aminobutyric acid (GABA)-mimetic molecules that are uniquely associated with the surfaces of crustose red algae (9, 10). These purified natural inducers alone, GABA, and a number of GABA analogs are sufficient to induce this genetically programed behavioral and morphogenetic sequence (11-14); in the absence of such inducers, the larvae do not settle or metamorphose (11)(12)(13)(14). Previous evidence had shown that recognition of these inducers by the Haliotis larvae is controlled by specialized chemosensory receptors located on the externally available larval epithelium (15-19); that the inducing signal is transduced by receptor-dependent changes in cAMP concentration (14) and an induced ion flux across the chemosensory membrane, producing an excitatory depolarization of the membrane (17); and that larval responsiveness to the GABA-mimetic signals can be reduced (or down-regulated) by habituation of the larvae prior to their development of competence to undergo settlement and metamorphosis (18).…”
Section: Introductionmentioning
confidence: 99%
“…The (+), (-), and racemic forms of the GABA analog P3-(p-chlorophenyl)-GABA (baclofen) were generous gifts from CIBA-Geigy. Haliotis larvae were produced and reared as described (11)(12)(13)(14). Spawning was induced by exposing gravid adult animals to hydrogen peroxide.…”
mentioning
confidence: 99%
See 2 more Smart Citations